The Canadian brothers, or, The prophecy fulfilled : a tale of the late American war - Richardson, Major (John), 1796-1852 (Centre for Editing Early Canadian Texts series, 1992)
Major John Richardson (1796-1852) was a prolific and popular Canadian author. The Canadian Brothers, first published in 1840 in Montreal, is set on the northwest frontier during the War of 1812 and features such historical personages as Sir Isaac Brock, Captain Robert Heriot Barclay, and the famous Indian chief Tecumseh. The sequel to Wacousta (1832), The Canadian Brothers is not only a suitably horrific completion to the story of vengeance and hate begun in Richardson's earlier novel. It is also, and most importantly, a fictionalized narrative of events, people, and places from Richardson's own childhood and adolescence in Amherstburg, Upper Canada, that both reveals the psychology of its author and reflects seminal mythologies about Ontario and Canada.